The effect of dopamine on response inhibition in Parkinson's disease relates to age-dependent patterns of nigrostriatal degeneration - Kübler D.; Schroll H.; Hamker F.; Joutsa J.; Buchert R.; Kühn A. (Elsevier Ltd, 2025)
Introduction: Motor but also non-motor effects are modulated by dopamine (DA) in Parkinson's disease (PD). Impaired inhibition has been related to dopamine overdosing of the associative striatum. We compared effects of dopaminergic medication on inhibitory control in patients with young (age at onset <50 years, YOPD) and late onset PD (LOPD) and related them to nigrostriatal degeneration.
Methods: 27 patients (10 YOPD, 17 LOPD) underwent a Go/NoGo paradigm comprising a global and specific NoGo condition ON and OFF DA. The ratio of dopamine transporter availability (DAT) in the associative relative to the sensorimotor striatum according to [123I]FP-CIT SPECT was compared between YOPD and LOPD (n = 8/12). Neuro-computational modeling was used to identify pathway activation during Go/NoGo performance.
Results: Patients made more errors ON compared to OFF in the global NoGo. This DA effect on global NoGo errors correlated with disease duration (r = 0.489, p = 0.010). YOPD made more errors in the specific NoGo ON-OFF compared to LOPD (p = 0.015). YOPD showed higher associative-to-sensorimotor DAT ratios compared to LOPD (p < 0.001). Neuro-computational modeling revealed DA overdosing of the associative striatum in YOPD resulting in excess activation of the direct basal ganglia pathway triggering incorrect responses.
Conclusions: Depending on the age of symptom onset, DA differentially modulated inhibition in PD with detrimental effects on specific NoGo performance in YOPD but increased performance in LOPD. YOPD showed relatively less degeneration in the associative striatum suggesting DA overdosing that is supported by our neuro-computational model. Reduced inhibition in the global NoGo condition suggests different pathway activation.